ADAPTIVE LEADERSHIP: CONCEPTS, MODELS AND THEIR ACTUALISATION IN EDUCATIONAL INSTITUTIONS - Mohamad Iwan Fitriani (El Midad, 2023)
The need for adaptive educational leadership is increasing along with the emergence of various challenges and demands experienced by educational institutions. Using a qualitative approach, this study aims to describe the concepts, models and practices of adaptive leadership. This study found that adaptive leadership is leadership that is able to respond to challenges faced quickly, precisely and relevantly. As a model, this adaptive leadership has similarities with flexible leadership. Both of these concepts can be applied in the context of education to create adaptive and flexible educational leadership. Furthermore, the implementation of adaptive leadership in education can be applied by; context analysis, schools’ leaders determine relevant strategies based on challenges faced, prepare Human Resources (HR), prioritize TEAM, determine policies, and monitor, evaluate and follow up the evaluation results. This study concludes that the adaptive leadership is needed to respond to dynamic realities as a consequence of organizational life and for unpredictable realities for the next better education quality